The First Year: Shifting Perceptions and Behaviours of Undergraduate Health Sciences Students’ Online Research Process - Galbraith, Susanna (Partnership, 2024)
This study investigates the perceptions and behaviours of novice academic researchers in their first year of post-secondary education when conducting online research. Conducting online research in this context describes what students anticipate they will do during an information search process and the strategies and tools they use in practice to locate information. Data from semi-structured interviews and process maps were analyzed to identify themes regarding the students’ perceptions and behaviours. While the participants were in university, they were providing a retrospective on past experience. Findings indicate that the experience of secondary students conducting research for school is one of frustration. Credible information is highly valued but difficult to obtain without the proper resources and skills. Students were initially hopeful that these frustrations would be appeased with access to better quality tools and learning the proper techniques of academic research. Because this study was undertaken immediately following the COVID-19 pandemic lockdowns of 2020–2022 it provides a unique window into how this experience impacted students and their choices and behaviours when conducting online research at the point of entering university and then further along in the first year. This exploratory research can serve to inform and provide insights into improving science and health sciences libraries’ user experience, instruction, marketing, and eresource collections, as well as students’ preparation for academic research in their secondary school years, particularly in the Canadian context.